Pas-kaart vande zee-kusten van Terra Nova : met de byleggende zee-kusten van Francia Nova, Canada en Accadie van C. de Sables tot de mond vande Straad Davids toe - Vooght, Claes Janszoon, -1696 (Amsterdam, vande Niewe-brugh inde Gekroonde, Loots-man (Netherlands), 1687)
Hand coloured. Decorative title cartouche. Two compass roses with rhumb lines. Depths shown by soundings. Bar scales in Dutch, Spanish, English and French miles. Shows underwater features.